2004
DOI: 10.1111/j.1365-2656.2004.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Age of primiparity and implications of early reproduction on life history in female Columbian ground squirrels

Abstract: Summary1. Factors leading to differences in age of primiparity and possible life-history implications arising from these differences were studied in a population of Columbian ground squirrels ( Spermophilus columbianus ; Ord, 1815). We used data collected from 1992 to 2000 on two neighbouring colonies of ground squirrels in south-eastern Alberta, Canada. 2. Earlier born females were more likely to wean successfully a litter at the age of 2. Among 2-year-old females, those who emerged earlier and heavier from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 39 publications
5
38
1
Order By: Relevance
“…Longevity was strongly correlated with the fitness measures used in our study, similar to results reported in several small as well as large mammals and birds (e.g., Kruuk et al 1999, von Holst et al 2002, Jensen and Miller 2004, Neuhaus et al 2004, Robbins et al 2011. The average age of female brown bears at primiparity is 4.7 years in our southern study area and 5.3 years in the northern study area (Zedrosser et al 2009).…”
Section: Discussionsupporting
confidence: 74%
“…Longevity was strongly correlated with the fitness measures used in our study, similar to results reported in several small as well as large mammals and birds (e.g., Kruuk et al 1999, von Holst et al 2002, Jensen and Miller 2004, Neuhaus et al 2004, Robbins et al 2011. The average age of female brown bears at primiparity is 4.7 years in our southern study area and 5.3 years in the northern study area (Zedrosser et al 2009).…”
Section: Discussionsupporting
confidence: 74%
“…Beyond the optimal age, any further enhancement of offspring survival would not be sufficient to justify the additional delay in reproduction. However, an early age of first parturition may have longer-term consequences, such as lower subsequent fecundity or shorter lifespan as reported for horseshoe bats (Ransome, 1995) and northern elephant seals (Reiter and Leboeuf, 1991), but not for southern elephant seals (Pistorius et al, 2004), rhesus macaques (Bercovitch and Berard, 1993), bighorn ewes (Festa-Bianchet et al, 1995), or Columbian ground squirrels (Neuhaus et al, 2004). Further study is needed to examine any long-term consequences of the age of first parturition in this species.…”
Section: Primiparous Femalesmentioning
confidence: 88%
“…Although differences between primiparous and multiparous females could reflect maternal experience, age-related patterns among primiparous females seem more likely to arise from differences in physical condition and/or maternal investment. Thus, although females of some species may not conceive until they reach a threshold weight (Festa-Bianchet et al, 1995;Bercovitch et al, 1998;Neuhaus et al, 2004;Setchell and Lee, 2004), the higher offspring mortality in primiparous mountain gorillas may reflect females who had not yet matured sufficiently for successful reproduction.…”
Section: Primiparous Femalesmentioning
confidence: 94%
“…Females who begin reproducing earlier should typically have more time for subsequent reproduction, unless the early start comes at the expense of harmful effects later in life (Ransome, 1995;Blomquist, 2009b). Studies generally have not discussed how human disturbances would influence this trade-off in other species, but assessments may be complicated by long-term environmental and demographic stochasticity and by differences in female quality (Bercovitch and Berard, 1993;Berube et al, 1999;Neuhaus et al, 2004;Descamps et al, 2006). Larger sample sizes are needed to evaluate this life history trade-off in mountain gorillas.…”
Section: Components Of Lrsmentioning
confidence: 97%